Kebijakan Hukum Pidana Terhadap Tindak Pidana Korupsi Pada Sektor Pelayanan Publik - Ture Ayu Situmeang; Ivana Theo Philia; Reh Bungana Br. PA; Maulana Ibrahim (Universitas Sains dan Teknologi Komputer, 2023)
Corruption is a criminal act committed by a person or an organization whose position and financial power allow him to abuse his power. These actions can harm a party, organization or country. Prevention and response through law enforcement must be carried out comprehensively so that law enforcement can be effective. The aim of this research is to examine the extent of criminal law policies in criminal acts of corruption in the public service sector. This research is descriptive in nature with a normative legal research type. Data was collected using library research and then analyzed qualitatively.